Statistical computing in nuclear imaging - Sitek, Arkadiusz (Series in medical physics and biomedical engineering., 2015)
Basic Statistical Concepts Introduction Before- and After-the-Experiment ConceptsDefinition of ProbabilityJoint and Conditional ProbabilitiesStatistical Model Likelihood Pre-Posterior and Posterior Extension to Multi-Dimensions Unconditional and Conditional IndependenceSummaryElements of Decision Theory Introduction Loss Function and Expected Loss After-the-Experiment Decision Making Before-the-Experiment Decision MakingRobustness of the Analysis Counting Statistics Introduction to Statistical Models Fundamental Statistical Law Exact Models of Photon-Limited DataPoisson Approximation Normal Di.